Solve the following systems of equations by substitution method.

1) y = -2 and 4x - 3y = 18

IF YOU WANT TO ANSWER MORE: HERE IS THE REST PART OF THE QUESTION—

2) y = 6x - 11 and 2x + 3y = 7

3) x = -3y - 5 and 4x - 5y = -3

4) x = 5y - 7 and -2x - 3y = -12

5) 5x - 3y - 8 = 0 and 2x - 3y - 6 = 0

6) x - 3y - 11 = 0 and 5x + y - 7 = 0

7) 2x - 3y = -1 and y = x - 1

8) -4x + y = 6 and -5x - y = 21

Respuesta :

Answer:

1) x = 3 and y = -2

2) x = 2 and y = 1

3) x = -2 and y = -1

4) x = 3 and y = 2

5) x = 2

6) x = 2 and y = -3

7) x = 4 and y = 3

8) x = -3 and y = -6

Step-by-step explanation:

1. Answer :

y = -2

4x - 3y = 18 ----(1)

Substitute y = -2 in (1).

4x - 3(-2) = 18

4x + 6 = 18

Subtract 6 from both sides.

4x = 12

Divide both sides by 4.

x = 3

So,

x = 3 and y = -2

2. Answer :

y = 6x - 11 ----(1)

2x + 3y = 7 ----(2)

Substitute y = 6x - 11 in (2).

2x + 3(6x - 11) = 7

2x + 18x - 33 = 7

20x - 33 = 7

Add 33 to both sides.

20x = 40

Divide both sides by 20.

x = 2

Substitute x = 2 in (1).

y = 6(2) - 11

= 12 - 11

= 1

So,

x = 2 and y = 1

3. Answer :

x = -3y - 5 ----(1)

4x - 5y = -3 ----(2)

Substitute x = -3y + 5 in (2).

4(-3y - 5) - 5y = -3

-12y - 20 - 5y = -3

-17y - 20 = -3

Add 20 to both sides.

17y = -17

Divide both sides by 17.

y = -1

Substitute y = -1 in (1).

x = -3(-1) - 5

= 3 - 5

= -2

So,

x = -2 and y = -1

4. Answer :

x = 5y - 7 ----(1)

-2x - 3y = -12 ----(2)

Substitute x = 5y - 7 in (2).

-2(5y - 7) - 3y = -12

-10y + 14 - 3y = -12

-13y + 14 = -12

Subtract 14 from both sides.

-13y = -26

Divide both sides by -13.

y = 2

Substitute y = 2 in (1).

x = 5(2) - 7

= 10 - 7

= 3

So,

x = 3 and y = 2

5. Answer :

5x + 3y - 8 = 0 ----(1)

2x - 3y - 6 = 0 ----(2)

Solve for 3y in (1).

5x + 3y - 8 = 0

Subtract 5x from both sides.

3y - 8 = -5x

Add 8 to both sides.

3y = -5x + 8

Substitute 3y = -5x + 8 in (2).

2x - (-5x + 8) - 6 = 0

2x + 5x - 8 - 6 = 0

7x - 14 = 0

Add 14 to both sides.

7x = 14

Divide both sides by 7.

x = 2

6. Answer :

x - 3y - 11 = 0 ----(1)

5x + y - 7 = 0 ----(2)

Solve for x in (1).

x - 3y - 11 = 0

Subtract 3y and 11 to both sides.

x = 3y + 11 ----(3)

Substitute x = 3y + 11 in (2).

5(3y + 11) + y - 7 = 0

15y + 55 + y - 7 = 0

16y + 48 = 0

Subtract 48 from both sides.

16y = -48

Divide both sides by 16.

y = -3

Substitute y = -3 in (3).

x = 3(-3) + 11

= -9 + 11

= 2

So,

x = 2 and y = -3

7. Answer :

2x - 3y = -1 ----(1)

y = x - 1 ----(2)

Substitute y = x - 1 in (1).

2x - 3(x - 1) = -1

2x - 3x + 3 = -1

-x + 3 = -1

Subtract 3 from both sides.

-x = -4

Multiply both sides by -1.

x = 4

Substitute x = x in (3).

y = 4 - 1

= 3

So,

x = 4 and y = 3

8. Answer :

-4x + y = 6 ----(1)

-5x - y = 21 ----(2)

Solve for y in (1).

-4x + y = 6

Add 4x to both sides.

y = 4x + 6 ----(3)

Substitute y = 4x + 6 in (2).

-5x - (4x + 6) = 21

-5x - 4x - 6 = 21

-9x - 6 = 21

Add 6 to both sides.

-9x = 27

Divide both sides by -9.

x = -3

Substitute x = -3 in (3).

y = 4(-3) + 6

= -12 + 6

= -6

So,

x = -3 and y = -6

Learn more:

brainly.com/question/26555025

Social studies

brainly.com/question/26539371

Mathematics

brainly.com/question/26537282

Divisibility - Math

brainly.com/question/26525264

Mathematics

Thank You!

Answered by: ms115

Answer:

See below for all answers and explanations

Step-by-step explanation:

Problem 1

4x - 3y = 18

4x - 3(-2) = 18 <-- Substituting y = -2

4x + 6 = 18

4x = 12

x = 3

Problem 2

2x + 3y = 7

2x + 3(6x-11) = 7 <-- Substituting y = 6x - 11

2x + 18x - 33 = 7

20x - 33 = 7

20x = 40

x = 2

y = 6x - 11 <-- Substituting x=2 to solve for y

y = 6(2) - 11

y = 12 - 11

y = 1

Problem 3

4x - 5y = -3

4(-3y-5) - 5y = -3 <-- Substituting x = -3y - 5

-12y - 20 - 5y = -3

-17y - 20 = -3

-17y = 17

y = -1

x = -3y - 5 <-- Substituting y = -1 to solve for x

x = -3(-1) - 5

x = 3 - 5

x = -2

Problem 4

-2x - 3y = -12

-2(5y-7) - 3y = -12 <-- Substituting x = 5y - 7

-10y + 14 - 3y = -12

-13y + 14 = -12

-13y = -26

y = 2

x = 5y - 7 <-- Substituting y=2 to solve for x

x = 5(2) - 7

x = 10 - 7

x = 3

Problem 5

5x - 3y - 8 = 2x - 3y - 6 <-- Setting equations equal to each other

5x - 8 = 2x - 6 <-- Eliminating y-variable to solve for x

3x - 8 = -6

3x = 2

x = 2/3

5x - 3y - 8 = 0 <-- Substituting x = 2/3 into first equation

5(2/3) - 3y - 8 = 0

10/3 - 3y - 8 = 0

10/3 - 3y - 24/3 = 0

-14/3 - 3y = 0

-3y = 14/3

y = -14/9

Problem 6

x - 3y - 11 = 0 <-- Solve for x

x - 3y = 11

x = 11 + 3y

5x + y - 7 = 0

5(11+3y) + y - 7 = 0 <-- Substituting x = 11 + 3y

55 + 15y + y - 7 = 0

55 + 16y - 7 = 0

48 + 16y = 0

16y = -48

y = -3

x = 11 + 3y <-- Substitute y=-3 into first equation to solve for x

x = 11 + 3(-3)

x = 11 - 9

x = 2

Problem 7

2x - 3y = - 1

2x - 3(x-1) = -1 <-- Substituting y = x - 1

2x - 3x + 3 = -1

-x + 3 = -1

-x = -4

x = 4

y = x - 1 <-- Substitute x=4 to solve for y

y = 4 - 1

y = 3

Problem 8

-4x + y = 6 <-- Solve for y in first equation

y = 6 + 4x

-5x - y = 21

-5x - (6+4x) = 21 <-- Substituting y = 6 + 4x

-5x - 6 - 4x = 21

-9x - 6 = 21

-9x = 27

x = -3

y = 6 + 4x <-- Substitute x = -3 to solve for y

y = 6 + 4(-3)

y = 6 - 12

y = -6